2023
DOI: 10.1021/acsomega.2c05607
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Fast, Quantum Mechanics-Based Approximation of Drug Lipophilicity

Abstract: Lipophilicity, as measured by the partition coefficient between octanol and water (log P), is a key parameter in early drug discovery research. However, measuring log P experimentally is difficult for specific compounds and log P ranges. The resulting lack of reliable experimental data impedes development of accurate in silico models for such compounds. In certain discovery projects at Novartis focused on such compounds, a quantum mechanics (QM)-based tool for log P estimation has emerged as a valuable supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 83 publications
(191 reference statements)
4
22
0
Order By: Relevance
“…361 Focused on drug lipophilicity, rescoss_logp_ml was developed to predict log P for a given molecule. 362 Including liquid chromatography retention time as a molecular descriptor for training, the multilayer perceptron p_chem_prop_CEVR computes log P and the distribution coefficient log D. 363 Ionization Energies. The IonEner-Pred GitHub repository contains fourteen different conventional and GNN models that can compute ionization energies.…”
Section: A Foray Into Additional Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…361 Focused on drug lipophilicity, rescoss_logp_ml was developed to predict log P for a given molecule. 362 Including liquid chromatography retention time as a molecular descriptor for training, the multilayer perceptron p_chem_prop_CEVR computes log P and the distribution coefficient log D. 363 Ionization Energies. The IonEner-Pred GitHub repository contains fourteen different conventional and GNN models that can compute ionization energies.…”
Section: A Foray Into Additional Topicsmentioning
confidence: 99%
“…Using the DeepChem library, log_P_prediction uses convoluted graphs and an NN to predict the octanol–water partition coefficient (i.e., log P) . Focused on drug lipophilicity, rescoss_logp_ml was developed to predict log P for a given molecule . Including liquid chromatography retention time as a molecular descriptor for training, the multilayer perceptron p_chem_prop_CEVR computes log P and the distribution coefficient log D …”
Section: A Foray Into Additional Topicsmentioning
confidence: 99%
“…For example, Isert et al reported that ML can be learnt on calculated log K o/w values to obtain a computationally affordable, QM-based estimation of lipophilicity. 77 Thus, AI and QM have a shared future that can benefit in silico toxicology, so long as we keep in mind their fundamental differences and limitations. In this regard, while QM has evolved in the Darwinian sense from human knowledge and understanding of the natural world and has been extensively tested over the past nearly 100 years, AI is a difficult-to-verify construct of the machine world that requires large data to ensure robustness.…”
Section: Implementationsmentioning
confidence: 99%
“…In the same vein as the two studies above, AI can be used to target physicochemical properties derived from molecular energy. For example, Isert et al reported that ML can be learnt on calculated log K o/w values to obtain a computationally affordable, QM-based estimation of lipophilicity . Thus, AI and QM have a shared future that can benefit in silico toxicology, so long as we keep in mind their fundamental differences and limitations.…”
Section: The Road Aheadmentioning
confidence: 99%
“…The resurgence of ML in chemistry has been fuelled by increased storage capacity, powerful hardware, and a wealth of data to delve on. Tasks that were once demanding to machines, e.g., retrosynthetic planning, 5-7 molecular design, 8-10 prediction of protein structure and function, [11][12][13] prediction of biological activity [14][15][16] and others, [17][18][19] have now become signicantly more attainable and generalizable, providing valuable assistance to bench chemists. 20 ML workows and pipelines are primarily implemented to accelerate chemical research, with the scope of prioritizing experiments with high condence and likelihood of success, while minimizing exploration towards preestablished objectives.…”
Section: Introductionmentioning
confidence: 99%